Negative pressure characteristics of an evaporating meniscus at nanoscale - Maroo Shalabh; Chung JN (Nanoscale Research Letters, 2011)
Abstract This study aims at understanding the characteristics of negative liquid pressures at the nanoscale using molecular dynamics simulation. A nano-meniscus is formed by placing liquid argon on a platinum wall between two nano-channels filled with the same liquid. Evaporation is simulated in the meniscus by increasing the temperature of the platinum wall for two different cases. Non-evaporating films are obtained at the center of the meniscus. The liquid film in the non-evaporating and adjacent regions is found to be under high absolute negative pressures. Cavitation cannot occur in these regions as the capillary height is smaller than the critical cavitation radius. Factors which determine the critical film thickness for rupture are discussed. Thus, high negative liquid pressures can be stable at the nanoscale, and utilized to create passive pumping devices as well as significantly enhance heat transfer rates.